Silent But Obstructive: Tracheal Polyp Mimicking Common Respiratory Disease - Sutanegara, Bagus Agung Arya Dharma Pramana Dwi; Wiguna, I Gede Arya Yoga Dharma; Pratama, I Putu Angga Manik; Yani, Luh Gede Janny Resista; Putra, Wayan Wahyu Semara; Novitasari, Novitasari (Riviera Publishing, 2026)
Central airway obstruction is a potentially life-threatening condition that may arise from malignant or benign pathologies. Benign tracheal tumors are exceptionally uncommon, constituting less than 2% of airway lesions, with fibroepithelial polyps representing one of the rarest variants. Their clinical manifestations are often nonspecific and may be mistaken for common respiratory disorders, contributing to delayed diagnosis. This report presents a rare case of a benign tracheal polyp presenting as central airway obstruction in an adult smoker and highlights the importance of early diagnostic evaluation. Case: A 41-year-old male smoker presented with progressive dyspnea, productive cough, chest discomfort, weight loss, and intermittent fever. Physical examination revealed mild rhonchi without wheezing or stridor. Arterial blood gas showed respiratory acidosis (pH 7.32; pCO? 50 mmHg). Chest X-ray revealed only bronchitic changes, but computed tomography identified an intraluminal mass at the T1–T2 level. Bronchoscopy revealed a nearly occlusive, pedunculated tracheal lesion. The patient was scheduled for bronchoscopic biopsy and debulking. Histopathological examination revealed a benign mesenchymal tumor with prominent thick-walled blood vessels, consistent with a glomus tumor. No malignant cells were identified. Bronchoscopic debulking successfully restored airway patency. This case underscores the importance of considering rare benign tracheal lesions in adult smokers who present with persistent respiratory symptoms refractory to standard management. Early cross-sectional imaging and bronchoscopic evaluation are essential for establishing a definitive diagnosis. Bronchoscopic intervention offers a safe and effective minimally invasive approach for restoring airway patency in patients with fibroepithelial tracheal polyps, thereby preventing critical airway compromise.